Produção e caracterização da enzima frutosiltransferase de Aspergillus oryzae IPT-301 visando a obtenção de frutooligossacarídeos - Cunha, Josivan De Sousa (2017)
Fructooligosaccharides (FOS) are fructose oligomers in which the fructosyl units are bound in β-(2→1) position of sucrose molecule. These sugars, that present properties such as low caloric value and non-cariogenicity, are classified as prebiotics and can be used in diabetic products; they are 0.4 to 0.6 times less sweet than sucrose, being widely applied in the pharmaceutical and food industries as functional sugars. Despite the natural production of FOS by enzymes present in various vegetables, they are commercially available by synthetic production, using microbial enzymes such as fructosyltransferases (FTases, E.C.2.4.1.9) and sucrose as main substrate. In face of this context, the objective of the present study was the production of extracellular and mycelium FTases by Aspergillus oryzae IPT-301 from aerobic submerged fermentation using synthetic growth media, as well as the characterization of the enzymes produced and the conduction of kinetic studies. It was also investigated the temperature and pH effects of the growth media in the enzymatic activities through experimental planning. For FTases production was necessary the use of sterile growth media, and the fermentation was carried out in rotary shaker. With the filtered broth and the humid mycelium it was possible to determine the transfructosylation and hydrolytic activities of the extracellular and mycelium enzymes in different experimental conditions; the transfructosylation activity was defined as the amount of enzyme necessary to produce 1 µmol of FOS per minute under the experimental conditions, while the hydrolytic activity was defined as the amount of enzyme necessary to release 1 µmol of fructose per minute under the experimental conditions. The maximum biomass concentration (9.35 ± 1.26 g.L-1) was obtained in 48 h of fermentation; in 76 h there was a biomass production of 7.51 ± 1.57 g.L-1 and the acidification of the fermented broth (pH 4.82). The conditions in which was observed the maximum transfructosylation activity of the extracellular enzyme were 64 h of fermentation, pH range of 4.5 to 6.0, reactional temperature of 50 °C and sucrose concentration from 296.0 g.L-1; the thermal stability was between 30 and 35 °C and pH 6.0. On the other hand, mycelium FTase had its optimum in 72 h of fermentation, pH range of 4.5 to 6.0, reactional temperature between 45-55 °C and substrate concentration of 470.6 g.L-1; the thermal stability was between 30 and 40 °C and pH range 6.0 to 8.0. Extracellular FTase presented michaelian kinetic according to substrate concentration, showing Vmax and Km values of 16.23 U.mL-1 and 50.41 g.L-1, while micelial FTase fitted to Hill Model, whose Vmax, K0,5 e n values was 342.23 U.g-1 e 234.73 g.L-1 and 1.41, respectively. The study of reaction’s time and temperature showed that extracellular FTase produced a maximum concentration of FOS at 50 °C, while the micelial one at 40 °C. The process optimization for FOS production verified that the optimum zone for extracellular FTase, in which are expected high transfructosylation and low hydrolytic activities, occurred in temperature range of 45 - 50 °C and pH range of 5.5 - 6.75. For mycelium FTase, only the transfructosylation activity presented a satisfactory adjustment to the quadratic model with interaction, in which the optimum zone occurred in temperatures above 46 °C and pH values below 6.5. The results obtained showed that the fungus stood out as source of FTase, and these enzymes presented themselves as promising sources for FOS production in laboratorial scale.